The effects of estuarine wetlands on flood losses associated with storm surge. (1st May 2018) - Highfield, Wesley E.; Brody, Samuel D.; Shepard, Christine
Abstract: Wetlands are frequently cited for their ability to reduce the adverse effects of flooding. Despite the growing negative impacts of storm surge and tidal flood events on coastal communities in the United States (U.S.), little if any, systematic, observation-based work has been done that measures the effects of estuarine wetlands in reducing actual flood loss. This study quantitatively assesses the role of estuarine and tidal wetlands in mitigating the amount of surge-induced flood damage experienced on Galveston Island by Hurricane Ike in 2008. Using a novel approach to measuring potential wetland influence, statistical analysis is performed on site-level flood damage observations to detect under which locations and configurations naturally-occurring estuarine wetlands might reduce impacts to residential structures. Results suggest that tidal wetlands may reduce storm-surge induced flood damage under certain distance and location characteristics, yet increase damage in others. Specifically, structures that were within 500' and sheltered by tidal wetlands demonstrated decreased flood damage, however damages increased at distances beyond this threshold, relative to non-sheltered structures. These results provide critical information to the debate on the effectiveness of wetlands for coastal flood mitigation and provide guidance to local decision makers interested in facilitating the development of more flood resilient communities over the long term. Highlights: The effect of estuarine wetlands on site-level flood damage is statistically analyzed. Potential wetland influence is measured based on distance and relative position. Results indicate that estuarine wetlands have detectable but moderate effect on flood damage.